The Role of Teaching Compounds According to Types of Speech in Constructivism (Eurasian Journal of Learning and Academic Teaching, 2022)
This article is dedicated to compare and analyze the compound words of Uzbek, English, to classify the compounds according to morphological and lexical point of view in constructivism.